2023
DOI: 10.1371/journal.pone.0281887
|View full text |Cite
|
Sign up to set email alerts
|

Methods to extract and study the biological effects of murine gut microbiota using Caenorhabditis elegans as a screening host

Abstract: Gut microbiota has been established as a main regulator of health. However, how changes in gut microbiota are directly associated with physiological and cellular alterations has been difficult to tackle on a large-scale basis, notably because of the cost and labor-extensive resources required for rigorous experiments in mammals. In the present study, we used the nematode Caenorhabditis elegans as a model organism to elucidate microbiota-host interactions. We developed a method to extract gut microbiota (MCB) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…In this context, a recent study demonstrated that supplementation with gut microbiota (MCB) from murine feces represented lower energy density (glucose and triglycerides) in comparison with E. coli OP50. Consequently, MCB-fed worms exhibited smaller body length and size, lower fertility, lower fat content, and an extended lifespan in comparison to those fed with the standard diet [65]. Moreover, Gu et al demonstrated the differential fatty acid composition of C. elegans exposed to E. cloacae in comparison with E. coli OP50 [36].…”
Section: Study Limitationsmentioning
confidence: 99%
“…In this context, a recent study demonstrated that supplementation with gut microbiota (MCB) from murine feces represented lower energy density (glucose and triglycerides) in comparison with E. coli OP50. Consequently, MCB-fed worms exhibited smaller body length and size, lower fertility, lower fat content, and an extended lifespan in comparison to those fed with the standard diet [65]. Moreover, Gu et al demonstrated the differential fatty acid composition of C. elegans exposed to E. cloacae in comparison with E. coli OP50 [36].…”
Section: Study Limitationsmentioning
confidence: 99%
“…Testing C. elegans with different gut microbiota or E. coli OP50 shows differences in growth and lifespan. C. elegans fed on murine gut microbes show reduction in diet preference, body size, fecundity, as well as carbohydrate and lipid content, yet these worms exhibit longer lifespans, similar to the influence of diet restriction in mammals [ 25 ]. C. elegans is also used for studying human infection with pathogens [ 26 , 27 ] and for screening drug–microbe interactions [ 28 ].…”
Section: Experimental Approaches For Studying the C Elegans...mentioning
confidence: 99%